Infectious bursal disease virus infection leads to changes in the gut associated-lymphoid tissue and the microbiota composition - Li, Li; Kubasová, Tereza; Rychlik, Ivan; Hoerr, Frederic J; Rautenschlein, Silke (PloS one, 2018)
Infectious bursal disease (IBD) is an acute, highly contagious and immunosuppressive poultry disease. IBD virus (IBDV) is the causative agent, which may lead to high morbidity and mortality rates in susceptible birds. IBDV-pathogenesis studies have focused mainly on primary lymphoid organs. It is not known if IBDV infection may modify the development of the gut associated lymphoid tissues (GALT) as well as the microbiota composition. The aim of the present study was to investigate the effects of IBDV-infection on the bursa of Fabricius (BF), caecal tonsils (CT) and caecum, and to determine the effects on the gut microbiota composition in the caecum. Commercial broiler chickens were inoculated with a very virulent (vv) strain of IBDV at 14 (Experiment 2) or 15 (Experiment 1) days post hatch (dph). Virus replication, lesion development, immune parameters including numbers of T and B lymphocytes, macrophages, as well as the gut microbiota composition were compared between groups. Rapid IBDV-replication was detected in the BF, CT and caecum. It was accompanied by histological lesions including an infiltration of heterophils. In addition a significant reduction in the total mucosal thickness of the caecum was observed in vvIBDV-infected birds compared to virus-free controls (P < 0.05). vvIBDV infection also led to an increase in T lymphocyte numbers and macrophages, as well as a decrease in the number of B lymphocytes in the lamina propria of the caecum, and in the caecal tonsils. Illumina sequencing analysis indicated that vvIBDV infection also induced changes in the abundance of Clostridium XIVa and Faecalibacterium over time. Overall, our results suggested that vvIBDV infection had a significant impact on the GALT and led to a modulation of gut microbiota composition, which may lead to a higher susceptibility of affected birds for pathogens invading through the gut.
Keywords: infekce viry z čeledi Birnaviridae; kur domácí; Animals; Infectious bursal disease virus; lymfoidní tkáň; Poultry Diseases; mikrobiota; zvířata; virus infekční bursitidy drůbeže; Lymphoid Tissue; Microbiota; cékum; nemoci drůbeže; Cecum; Chickens; Birnaviridae Infections